Fisheries biology, assessment and management - King, Michael (Blackwell Pub., 2007)
The main differences between the first and second editions relate to an updating of the text in the light of recent developments in fisheries technology, stock assessment methods and management practices, along with the addition of a chapter covering general aspects of marine ecology. King's book is most suitable for undergraduate courses in fisheries biology/science, and caters for the needs of students who may have little prior knowledge of aquatic biology